Body Mass Index at Pediatric Leukemia Diagnosis and the Risks of Relapse and Mortality: Findings from a Single Institution and Meta-analysis - Ashleigh M. Saenz; Stacie Stapleton; Raquel G. Hernandez; Greg A. Hale; Neil A. Goldenberg; Skai Schwartz; Ernest K. Amankwah (Journal of Obesity)
High body mass index (BMI) is associated with relapse of certain adult cancers, but limited knowledge exists on its association with pediatric leukemia relapse. We evaluated the association between overweight/obesity (BMI ≥ 85th percentile) at pediatric leukemia diagnosis and relapse or mortality. A meta-analysis combining our findings with those of previous studies was also performed. The study included 181 pediatric leukemia patients. Sporadic missing data were multiply imputed, and hazard ratios (HR) and 95% confidence intervals (95% CI) were calculated using Cox proportional hazard. Age- and sex-adjusted analysis for patients ≥10 years showed a trend towards increased risk of relapse for overweight/obese patients (HR = 2.89, 95% CI = 0.89–9.36, p=0.08) that was not evident among children<10 years (HR = 0.52, 95% CI = 0.08–3.54, p=0.49). We observed a statistically significant association between mortality and obesity status in unadjusted models (imputed: HR = 2.54, 95% CI = 1.15–5.60, p=0.021; complete set: HR = 2.72, 95% CI = 1.26–5.91, p=0.011) that was not statistically significant in both age- and sex-adjusted and multivariable adjusted analyses. The pooled estimate of our finding and previous studies showed an association between overweight/obese and increased risk of mortality for ALL (HR = 1.39, 95% CI = 1.16–1.46) and AML (HR = 1.64, 95% CI = 1.32–2.04). Although our study did not observe statistically significant associations due to a small sample size, the meta-analyses revealed an increased risk of mortality for overweight/obese patients. The findings of our study suggest an association of obesity status with relapse in children ≥10 years. However, our study was based on a small sample size from a single institution, and this association needs to be investigated in larger, multicenter studies.